2021
DOI: 10.1016/j.ypmed.2021.106735
|View full text |Cite
|
Sign up to set email alerts
|

Suicide in late life: A viewpoint

Abstract: Suicide in old age represents a sad public health concern. Despite the global decline in rates of suicide and the general amelioration of quality of life and access to health care for older adults, their rates of suicide remain the highest virtually in every part of the world. With the aging of the world population and the growing number of mononuclear families, the risk of an increase in isolation, loneliness and dependency does not appear ungrounded. The Covid-19 pandemic is claiming the life of many older p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 143 publications
(159 reference statements)
1
9
0
4
Order By: Relevance
“…It was reported that the lifetime prevalence rate of mental ill-health – (depression & traumatic stress) in South Africa was 2.3 percent and 4.9 percent, respectively ( Swain et al, 2017 , Peltzer and Phaswana-Mafuya, 2013 ). These figures are lower than the global average ( De Leo and Giannotti, 2021 ) – characterized by low pension coverage for the elderly population. There is a possibility that the expanding social pension coverage in South Africa is responsible for improving depression & traumatic stress.…”
Section: Introductionmentioning
confidence: 69%
“…It was reported that the lifetime prevalence rate of mental ill-health – (depression & traumatic stress) in South Africa was 2.3 percent and 4.9 percent, respectively ( Swain et al, 2017 , Peltzer and Phaswana-Mafuya, 2013 ). These figures are lower than the global average ( De Leo and Giannotti, 2021 ) – characterized by low pension coverage for the elderly population. There is a possibility that the expanding social pension coverage in South Africa is responsible for improving depression & traumatic stress.…”
Section: Introductionmentioning
confidence: 69%
“…Lastly, some degree of misclassification is expected, especially at older ages, 41 as suicide could be misclassified as an “accidental”, “unknown”, or “undetermined” cause of death. Although this misclassification is expected to cause a general underestimation without affecting the comparisons across the characteristics investigated, 42 it should be considered that underreporting could be larger at very old ages, when the prevalence of physical illness is higher than in younger age groups 43 and deaths due to self‐starvation or self‐dehydration could be not counted as suicides 44 …”
Section: Discussionmentioning
confidence: 99%
“…Usia yang lebih tua cenderung merencanakan tindakan dengan lebih hati-hati dan mengatur secara detail prosedur yang memiliki kemungkinan besar untuk berhasil. (Leo and Viecelli, 2020) Data menunjukkan bahwa meskipun angka kematian akibat bunuh diri telah menurun sebesar 32,7% dari tahun 1990 hingga 2016, namun angka bunuh diri di kalangan lansia masih tinggi di seluruh dunia. Diperkirakan insiden bunuh diri terjadi pada 27,45 per 100.000 penduduk berusia >70, dan 16,17 orang per 100.000 penduduk pada kelompok usia 50-69 tahun.…”
Section: Pendahuluanunclassified